Argumentative Techniques in the Cultural Supplement of Al-Watan Newspaper (Issues 1–30): A Pragmatic Study - Al-Qarni, Abdulmajid Bin Saad Bin Bishi (Arts for Linguistic & Literary Studies, 2025)
This research explores argumentative techniques in the cultural supplement of Al-Watan newspaper, focusing on issues (1–30), within a pragmatic framework informed by Perelman and Olbrechts-Tyteca’s New Rhetoric. By analyzing both critical essays and satirical caricatures, the study highlights the newspaper’s role as a cultural channel and a medium of transformation, where persuasive discourse is a central tool. The research integrates journalistic culture with the pragmatic functions of argumentation, demonstrating how quasi-logical reasoning, rhetorical figures, and other argumentative strategies are employed to influence readers. Through an introduction and two main sections—one addressing argumentative mechanisms and the other examining argumentative techniques—the study reveals that the newspaper largely employs argumentation aimed at persuasion and impact, whether through rejecting negative issues, promoting positive values, or presenting literary and cultural critique that broadens the reader’s capacity for reflection, interpretation, and critical engagement. Ultimately, the study underscores the cultural, literary, and social significance of Al-Watan’s cultural supplement as a space where journalism intersects with rhetoric and argumentation.